2018
DOI: 10.1111/cpr.12488
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin conjugated carbon dots as a drug delivery system for human breast cancer therapy

Abstract: The results of this study indicated that the CDs-DOX drug delivery system had a potential value in cancer chemotherapeutic application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 28 publications
0
69
1
Order By: Relevance
“… Citric acid and polyene polyamine (PEPA) Oxaliplatin Hepatic cancer cells [ 122 ] 10. Citric acid and ethylenediamine DOX L929, MCF-7 and CCK-8 [ 117 ] 11. Citric acid and diethylenetriamine PEG-(PAH/DMM) Cisplatin A2780 [ 11 ] 12.…”
Section: Applications Of Cdsmentioning
confidence: 99%
See 1 more Smart Citation
“… Citric acid and polyene polyamine (PEPA) Oxaliplatin Hepatic cancer cells [ 122 ] 10. Citric acid and ethylenediamine DOX L929, MCF-7 and CCK-8 [ 117 ] 11. Citric acid and diethylenetriamine PEG-(PAH/DMM) Cisplatin A2780 [ 11 ] 12.…”
Section: Applications Of Cdsmentioning
confidence: 99%
“…Recently Kong et al fabricated a citric acid and ethylenediamine based CDs for drug delivery systems. According to their results they observed that DOX could be quickly loaded on CDs through electrostatic interaction and the CDs/DOX complexes showed better cellular uptake and antitumor efficiency on the breast cancer MCF-7 cells compared with free DOX [ 117 ]. Similarly, some other researchers have also used CDs loaded with DOX for simultaneous cell imaging and drug delivery systems [ 27 , 114 , 118 120 ].…”
Section: Applications Of Cdsmentioning
confidence: 99%
“…DOX can also directly loaded on the surface of CDs for localized cancer therapy by simply mixing these CDs and DOX [127,128]. DOX can be released in the tumor acid microenvironment [129,130]. Chemotherapeutic DNA-modifying cisplatin and topoisomerase II-inhibiting DOX were conjugated on the full-color emissive CDs via a pH sensitive hydrazone bond [131].…”
Section: Fluorescent Cds Conjugated With Chemical Therapeutic Agentsmentioning
confidence: 99%
“…On the other hand, though a few articles have investigated both biodistribution and tumor targeting ability, the nanocarrier biodegradation capacity has not been thoroughly investigated. Prior to any clinical trial, the fate of any nanocarrier and its eventual persistence in the body must be addressed . Having conjugated fMLP to the surface of GO, the next objective of our work was to assess the biodegradation capacity of GOfMLP.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the design of site‐directed (targeted) drug delivery systems that can concentrate a higher amount of drug in the tumor area, inducing less side effects for healthy tissues, is at the forefront of research. Among targeted release systems, platforms with nanosized dimensions have exhibited great potential in biomedical applications . More specifically, graphene‐based materials (GBMs) have been extensively studied in this context …”
Section: Introductionmentioning
confidence: 99%